The relation between fault movement potential and seismic activity of major faults in Northwestern Vietnam - Duan, Bui Van; Duong*, Nguyen Anh (Vietnam Journal of Earth Sciences, 2017)
In this study, the method of Fault Movement Potential (FMP) proposed by Lee et al. (1997) is used to assess the movement potential of some major faults and its relationship with the seismic activities in Northwestern Vietnam. The fault movement potential is assessed by the magnitude of FMP (from 0 to 1) and calculated based on the relationship between kinematic characteristics of the faults and regional tectonic stress field. The maximum compressive stress axis in Northwestern Vietnam has the nearly horizontal trend (7.4±4.0) and the direction of 170.2±6.7. The calculated results of FMP at 60 geological survey points along major faults in Northwestern Vietnam show that the movement potential of these faults is mainly from medium to high (40/60 points with FMP = 0.6 - 0.9). In particular, the faults in Dien Bien Phu have the highest movement potential (FMP = 0.8 - 0.9). An earthquake catalog that consists of 177 earthquakes with M = 4.0 - 6.8 occurring in the studied area from 1277 to 2016 is used to assess the relationship between seismic activities and fault movement potential. The research results indicate that at the locations on the faults with high movement potential, seismic activities occur frequently. On the segment of Son La fault zone in Tuan Giao, Tua Chua, the movement potential has the highest value (FMP = 0.9), corresponding to the occurrence of Tuan Giao earthquake with M = 6.8 in 1983. On the contrary, weak earthquake or even no earthquake occur at the locations with low movement potential such as the segment of Son La fault in Moc Chau, Yen Chau, the segment of Ma River fault in Lang Chanh and the Than Uyen fault in Than Uyen. With the complete survey dataset on slip surface attitude of faults in contemporary times, FMP is significant for assessing the level of seismic activities on each part of the faults, serving the segmentation of faults, establishment of seismogenic regions, earthquake prediction and seismic hazard assessment. References Andeweg B., Vicente G. De , Cloetingh S., Giner J., and A. Muñoz Martin, 1999. Local stress field and intraplate deformation of Iberia: Variations in spatial and temporal interplay of regional stress sources, Tectonophysics, 305, 153-164. Angelier J., Tarantola A., Valette B., Manoussis S., 1982. Inversion of field data in fault tectonics to obtain the regional stress - I. Single phase fault populations: a new method of computing the stress tensor, Geophys. J. R. astr. Soc., 69, 607-621. Bui Van Duan, 2012. The study on contemporary tectonic characteristics and seismic activities in Muong La - Bac Yen fault zone. Master thesis, Hanoi University of Science, Hanoi (in Vietnamese). Bui Van Duan, Ha Thi Giang, Nguyen Anh Duong, and Pham Dinh Nguyen, 2015. About factors related to the occurrence of earthquakes in the Song Tranh 2 hydropower area in period 2011-2014. J. Sci. of the Earth, 37(3), 228-240 (in Vietnamese, abstract in English) Bott M.H.P., 1959. The mechanics of oblique slip faulting, Geol. Mag., 96, 109-117. Findlay R. H. and Phan Trong Trinh, 1997. The structural setting of Song Ma region, Vietnam and the Indochina-South China plate boundary problem. Gondwana Research, 1(1), 11-33. Ha Thi Giang, 2012. Determination of focal mechanisms of some earthquakes in North Vietnam using the broadband seismic data. Master thesis, Hanoi University of Science, Hanoi (in Vietnamese). He S.H., 1989. The Effect of Orientation and Level of Principal Stress on Fault Movement. Crustal Deformation and Earthquake, 9, 44-52. Le Tu Son, 2000. Focal mechanism of Ta Khoa, lai Chau and Muong Luan earthquake in North-West of Vietnam. J. Sci. of the Earth, 22(4), 355-360 (in Vietnamese, abstract English). Le Tu Son, 2004. The Dien Bien earthquake, Ms=5.3 on February 19, 2001. J. Sci. of the Earth, 26(2), 112-121 (in Vietnamese, Abstract English). Lee C.F., Hou J.J. and Ye H., 1997. The Movement Potential of the Major Faults in Hong Kong Area. Episodes, 20, 227-231. Lokajicek T., Spicak A., and Waniek L., 1988. Tectonic Stress Orientation and the Seismic Regime of a Single Fault. Tectonophysics, 152, 297-302. Maerten L., Gillespie P., Pollard D.D., 2002. Effects of local stress perturbation on secondary fault development. Journal of Structural Geology, 24, 145-153. Mandal P., Manglik A., Singh R.N., 1997. Intraplate stress distribution induced by topography and crustal density heterogeneities beneath the Killari, India. Journal of Geophysical Research, 102, 11719-11729. McKenzie D.P., 1969. The relation between fault plane solutions for earthquakes and the directions of the principal stresses, Bull. seism. Soc. Am., 59, 591-601. Moghimi H., Arian M., and Sorbi A., 2015. Fault Movement Potential of Marzanabad Area, North Alborz, Iran. Open Journal of Geology, 5, 126-135. Nguyen Anh Duong, Sagiya T., Kimata F., Tran D.T., Vy Q.H., Duong C.C., Nguyen X.B., and Nguyen D.X., 2013. Contemporary horizontal crustal movement estimation for northwestern Vietnam inferred from repeated GPS measurements, Earth Planets Space, 65(12), 1399-1410, DOI:10.5047/eps.2013.09.010. Nguyen Anh Duong, Fumiaki Kimata, Tran Dinh To, Nguyen Dinh Xuyen, Pham Dinh Nguyen, Vi Quoc Hai, Duong Chi Cong, 2011. Contemporary horizontal movement estimation for Lai Chau - Dien Bien fault inferred from repeated GPS measurements in 2002 - 2010. J. Sci. of the Earth, 33(4), 690-694 (in Vietnamese, abstract English), DOI:10.15625/0866-7187/33/4/556. Nguyen Dinh Xuyen et al., 2004a. Study on earthquake prediction and ground motion in Vietnam. Final report of the National project 2000-2002. Institute of Geophysics, Vietnam Academy of Science and Technology, Hanoi (in Vietnamese). Nguyen Dinh Xuyen et al., 2004b. Seismic hazard assessment and micro-zonation of Lai Chau hydropower dam area. Final report of the technical design stage. Institute of Geophysics, Vietnam Academy of Science and Technology, Hanoi (in Vietnamese). Nguyen Ngoc Thuy et al., 2005a. Detailed earthquake zoning for northwestern Vietnam, National Project on science and technology, KC08-10, Period 2001-2005, Institute of Geophysics, Hanoi, Vietnam, 2005 (in Vietnamese). Nguyen Ngoc Thuy et al., 2006. Seismic hazard assessment and micro-zonation of Van Chan hydropower dam area. Final report of the technical design stage. Institute of Geophysics, Vietnam Academy of Science and Technology, Hanoi (in Vietnamese). Nguyen Ngoc Thuy et al., 2008. Seismic hazard assessment, design earthquake parameters and micro-zonation of Hua Na hydropower dam area. Final report of the technical design stage. Institute of Geophysics, Vietnam Academy of Science and Technology, Hanoi (in Vietnamese). Nguyen Trong Yem, 1996. Tectonic stress field in Cenozoic in Vietnam. Journal of Geology (Hanoi), series A 236, 9-10 (in Vietnamese). Nguyen Van Hung, 2002. Some basic features of neotectonic faults in Northwestern Vietnam. Geological Doctoral Thesis, Institute of Geological Sciences, National Center for Natural Science and Technology, Hanoi (in Vietnamese). Nguyen Van Hung, Hoang Quang Vinh, 2004. On activity of neotectonic faults in Northwestern Vietnam. Journal of Geology (Hanoi), series A(285), 38-48 (in Vietnamese). Nguyen Van Luong, 1996. Results of determining focal mechanism by means of synthetic macroseismic field method in Vietnam. J. Sci. of the Earth, 18 (3), 145-152. Nguyen Van Luong and Bui Cong Que, 1997. Characteristics of the tectonic stress field of crust in the East Sea and adjacent areas. J. Sci. of the Earth, 19(1), 30-38 (in Vietnamese, abstract English). Nguyen Van Vuong, Vu Van Tich, Nguyen Ngoc Thuy, Bui Van Duan, 2004. Testing on the zonation and prediction of contemporary crustal movement features in Northwestern Vietnam based on the interrelation between the regional tectonic stress field and some fault systems. Journal of Geology (Hanoi), series A(285), 49-56 (in Vietnamese). Phan Trong Trinh, 1993. An inverse problem for the determination of the stress tensor from polyphased fault sets and earthquake focal mechanisms. Tectonophysics, 393-411. Phan Trong Trinh, 1994. Cenozoic stress field in the Northwestern region of Vietnam. Journal of Geology (Hanoi), series B (3-4), 12-18. Phan Trong Trinh, 2012. Neo-tectonics and contemporary geodynamics in Vietnam sea area and adjacency. Science and Technology Publishing House, Hanoi, 330p (in Vietnamese). Phan Trong Trinh, Hoang Quang Vinh, Nguyen Van Huong, Ngo Van Liem, 2013. Active fault segmentation and seismic hazard in Hoa-Binh reservoir, Vietnam. Central European Journal of Geosciences, 5(2). 223-235. DOI: 10.2478/s13533-012-0128-5. Phan Trong Trinh, Ngo Van Liem, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Bui Thi Thao, Mai Thanh Tan, Nguyen Hoang, 2012. Late Quaternary tectonics and seismotectonics along the Red River fault zone, North Vietnam. Earth Science Reviews 114 (3-4), 224-235. Phan Trong Trinh, Nguyen Trong Y., Nguyen H., Lacassin R., Tapponnier P., Leloup H. & Winter Th., 1994. Active faulting and tectonics of North Vietnam. International Workshop on Seismic Hazard in SE Asia, Hanoi, Vietnam. Reid H.F., 1910. The mechanics of the earthquake. In A.C. Lawson (Ed.), The California earthquake of April 18, 1906, Report of the State Earthquake Investigation Commission, Vol.II., Washington, DC: Carnegie Institute of Washington, 3-55. Reid H.F., 1911. The elastic rebound theory of earthquakes. Bulletin of the Department of Geology, University of California Publications 6(19), 413-444. Roman D.C. and Heron P., 2007. Effect of regional tectonic setting on local fault response to episodes of volcanic activity, Geophysical Research Letters, 34, L13310. Simons W.J.F., Socquet A., Vigny C., Ambrosius B.A.C., Haji Abu S., Chawat Promthong, Subarya C., Sasito D. A., Matheussen S., Morgan P., and Spakman W., 2007. A decade of GPS in Southeast Asia: Resolving Sundaland motion and boundaries, J. Geophys. Res., 112, B06420, DOI:10.1029/2005JB003868. Sorbi A., Arian M., Pourkermani M., 2009. The movement potential evaluation of the major Quaternary faults in Tehran Quadrangle. Journal of Sciences - Islamic Azad University (JSIAU), 19(73), 176-182. Tingay M., Morley C., King R., Hillis R., Coblentz D. & Hall R., 2010. Present-day stress field of Southeast Asia. Tectonophysics, 482(1-4), 92-104. Tran Van Thang et al., 2012. Study on the relationship between geological hazards and modern activity of sub-longitudinal tectonic fracture zones in Northwestern Vietnam. Final report of VAST project (2008-2009). Institute of Geological Sciences, Vietnam Academy of Science and Technology, Hanoi (in Vietnamese). Tuttle M.P., Schweig E.S., Sims J.D., Lafferty R.H., Wolf L.W., and Haynes M. L., 2002. The earthquake potential of the New Madrid seismic zone. Bull. Seismol. Soc. Am. 92, 2080-2089. Van Duc Tung, 2011. Development characteristics of the Lai Chau - Dien Bien fault zone. Geological Doctoral Thesis, Institute of Geological Sciences, Vietnam Academy of Science and Technology, Hanoi (in Vietnamese, Abstract English). Winter Th., Phan Trong Trinh, Lacassin R., Nguyen Trong Y., Costaz J., 1994. Advantages of a deterministic approach of seismic risk for dam design: the Hoa Binh Dam case (Vietnam). Proceedings of the International Workshop on Seismic Hazard in SE Asia, Hanoi, Vietnam, 249-254.